Tūhono : the United Collective : an exhibition report presented in partial fulfilment of the requirements for the degree of Masters of Māori Visual Arts, Massey University, Palmerston North, New Zealand - Hauraki, Glenn Douglas (Massey University, 2018)
This exhibition report provides a detailed outline of the pathway undertaken to complete the requirements of a Masters of Māori Visual Arts Thesis and the presentation of works 𝘛𝘶̄𝘩𝘰𝘯𝘰 in December 2017. 𝘛𝘶̄𝘩𝘰𝘯𝘰 explores the combination of tikanga Māori and customary techniques alongside modern and contemporary processes. The three pou whakairo were developed to align with the kaupapa 𝘛𝘦 𝘒𝘰𝘳𝘦, 𝘛𝘦 𝘗𝘰̄, and 𝘛𝘦 𝘈𝘰 𝘔𝘢̄𝘳𝘢𝘮𝘢. A range of tools and techniques, both traditional and contemporary were used to explore the medium.
Keywords: Glenn Douglas Hauraki; Criticism and interpretation; Wood-carving, Maori; Carving (Decorative arts); New Zealand; Whakairo; Research Subject Categories::HUMANITIES and RELIGION::Aesthetic subjects::Art